The analysis of medical rescue teams interventions due to sudden cardiac arrest in Brzesko District in years 2010–2012 - Urbaniak-Ostrykiewicz, Małgorzata; Wilk-Łoboda, Beata (Nursing in the 21st Century, 2013)
THE ANALYSIS OF MEDICAL RESCUE TEAMS INTERVENTIONS DUE TO SUDDEN CARDIAC ARREST IN BRZESKO DISTRICT IN YEARS 2010–2012Aim. The analysis of medical rescue teams interventions due to sudden cardiac arrest in Brzesko District in the years 2010-2012.Materials and method. Retrospective study was conducted in January and February 2013. In the study, the analysis of medical data, consisting of emergency dispatch cards, emergency procedure cards and resuscitation cards, was used. The retrospective analysis involved the documentation of medical rescue teams in Brzesko district in 2010, 2011 and 2012. There were 15 600 emergency dispatch cards  subjected to analysis, out of which 177 were isolated, where the cause of the intervention of medical rescue teams was cardiac arrest. Only those cases were analyzed, in which cardiopulmonary resuscitation was performed. The cases of death before the arrival of medical rescue team were excluded.Results. The data analysis proved that the number of medical rescue teams interventions due to sudden cardiac arrest in years 2010 and 2011 was comparable. In 2012, the decline in emergency calls for this kind of cases was noted. The majority of interventions was undertaken by specialized teams, on the basis of dispatcher’s decision, who - after receiving emergency call - decided on dispatching a team with a doctor. The median ambulance arrival time was in accordance with binding regulations. The least number of interventions took place at nighttime. More often sudden cardiac arrest concerned the men. The majority of cases in the years 2010 and 2011 was noted in the age range of 71-80; in 2012 – in the age between 61 and 70. The most common cause of cardiac arrest was sudden cardiac affliction (the most common mechanism leading to heart arrest was asystole). The procedures of medical rescue teams were in accordance with prescribed guidelines for cardiopulmonary resuscitation. The result of the majority of effective interventions undertaken by medical rescue teams was re-establishment of circulation. Unfortunately, in the majority of cases, the witnesses of the occurrence did not perform cardiopulmonary resuscitation activities.Conclusions:1. The leading cause of sudden cardiac arrest was cardiovascular disease.2. Sudden cardiac arrest concerned more often men than women.3. Cardiac arrest occurred  most often in a patient’s house.4. Unfortunately, almost 60% of witnesses of the occurrence did not perform resuscitation activities.5. The result of successfully conducted procedures was re-establishment of circulation.6. A specialized aid given by specialized “S” and basic “P” teams was in accordance with binding cardiac arrest policies.